EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION DAN PROBING-PROMPTING DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI ALJABAR DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI DI KABUPATEN KARANGANYAR - Kurniasari, Dewi; Kusmayadi, Tri Atmojo; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The objective of this research was to investigate the effect of learning model toward learning achievement in mathematics viewed from the mathematics anxiety. The learning models of this research were cooperative learning model of the GI with Scientific Approach, the cooperative learning model of the Probing-Prompting with Scientific Approach, and classical learning model with Scientific Approach. This was a quasi-experimental study with 3Ã3 factorical design. The study population was all eighth grade students of state junior high school in Karanganyar District. The sample was taken by using stratified cluster random sampling method. The sample consisted of 280 students with 95 students in the first experimental class, 93 students in the second experimental class, and 92 students in the control class. Instruments used to colled data were mathematics achievement test and the studentâs mathematics anxiety questionnaire. The proposed hypotheses of the research were tested by using the two-way analysis of variance with unbalanced cells. The results of the research were as follows: 1) GI cooperative learning model with scientific approach gave better achievement than probing-prompting with scientific approach and classical learning model with scientific approach while probing-prompting and classical learning model with scientific approach gave same achievement, 2) the students with low mathematics anxiety had better achievement than the students with moderate and high mathematics anxiety, and the students with moderate mathematics anxiety had better achievement than the students with high mathematics anxiety, 3) in all categories of studentâs mathematics anxiety, GI cooperative learning model with scientific approach, Probing-Prompting cooperative learning model with scientific approach, and classical learning model with scientific approach gave the same learning achievement in mathematics, 4) in the GI cooperative learning model with scientific approach and Probing-Prompting cooperative learning model with scientific approach, the students with low mathematics anxiety had better achievement than the students with moderate and high mathematics anxiety, and the students with moderate mathematics anxiety had better achievement than the students with high mathematics anxiety. In the classical learning model with scientific approach, the students with low mathematics anxiety had better achievement than the students with moderate and high mathematics anxiety, while the students with moderate and high mathematics anxiety had the same achievement.Keywords: Group Investigation (GI), Probing-Prompting, Classical Instruction, Scientific Approach, Mathematics Anxiety, Learning Achievement in Mathematics.